О. Д. Соколова-Пономарева, (1888-1966) - Бисярина Валентина Павловна (Выдающиеся деятели медицины, 1989)
Экземпляры: КХ (20110416) / Инвентарный номер: 933560 / Цена: 0.50 / Сис.шифр: 5 / Авт.знак: Б 65 / ГРНТИ: 76 / ББК: 5д